Technical Design and Financial Projection of Solar Power Plant on Grid 119.5 kWp in Sendang Sari Hotel - Kresna Pandu Pratama; Irwan Iftadi; Agus Ramelan (Universitas Sebelas Maret (UNS), 2023)
The productivity of a solar power plant is influenced by environmental factors such as the amount of irradiation captured, the amount of dust attached to it, and the ambient temperature. Therefore, it is very important to pay attention to the technical design of solar power plant, such as the installation location, tilt angle, and number of solar modules per series. In addition to a good technical design, it is also necessary to pay attention to its economic aspects, because solar power plant requires high costs, so it is necessary to make financial projections for the next few years, so that the economic value of the technical design can be determined. At this writing, the location is taken at Sendang Sari Hotel with coordinates -6.905910357088127, 109.72448291981084, installed power is 120kVA with the aim of the installation is for savings without exporting power to the grid. Based on the load analysis, the designed PLTS capacity is 119.5 kWp. Then, a simulation was carried out using the Helioscope which produced an energy yield of 161.8 MW with a performance ratio of 82.1%. Based on the simulation, a 25-year financial projection is obtained with an NPV of 580,943,546 IDR, an IRR of 6.09%, a payback period of 13.89 years, and an LCOE of 735.4 IDR/kWh.